A Novel Computational Method to Identify/Analyze Hysteresis Loops of Hard Magnetic Materials - Alessandro Giuseppe D’Aloia (Magnetochemistry, 2021)
In this study, a novel computational method capable of reproducing hysteresis loops of hard magnetic materials is proposed. It is conceptually based on the classical Preisach model but has a completely different approach in the modeling of the hysteron effect. Indeed, the change in magnetization caused by a single hysteron is compared here to the change in velocity of two disk-shaped solids elastically colliding with each other rather than the effect of ideal geometrical entities giving rise to so-called Barkhausen jumps. This allowed us to obtain a simple differential formulation for the global magnetization equation with a significant improvement in terms of computational performance. A sensitivity analysis on the parameters of the proposed method has indeed shown the capability to model a large class of hysteresis loops. Moreover, the proposed method permits modeling of the temperature effect on magnetization of neodymium magnets, which is a key point for the design of electrical machines. Therefore, application of the proposed method to the hysteresis loop of a real NdFeB magnet has been proven to be very accurate and efficient for a large temperature range.